Magnetotransport of single crystalline NbAs. (22nd April 2015) - Ghimire, N J; Luo, Yongkang; Neupane, M; Williams, D J; Bauer, E D; Ronning, F
Abstract We report transport measurement in zero and applied magnetic field on a single crystal of NbAs. Transverse and longitudinal magnetoresistance in the plane of this tetragonal structure does not saturate up to 9 T. In the transverse configuration (H ∥ c, I ⊥ c) it is 230 000% at 2 K. The Hall coefficient changes sign from hole-like at room temperature to electron-like below ∼150 K. The electron carrier density and mobility calculated at 2 K based on a single band approximation are 1.8 × 1019 cm−3 and 3.5 × 105 cm2 Vs−1, respectively. These values are similar to reported values for TaAs and NbP, and further emphasize that this class of noncentrosymmetric, transition-metal monopnictides is a promising family to explore the properties of Weyl semimetals and the consequences of their novel electronic structure.